Combining transcranial magnetic stimulation with training to improve social cognition impairment in schizophrenia: a pilot randomized controlled trial - Vergallito, Alessandra; Gramano, Bianca; La Monica, Kevin; Giuliani, Luigi; Palumbo, Davide; Gesi, Camilla; Torriero, Sara (Frontiers in Psychology, 2024)
Schizophrenia is a severe, chronic mental disorder that profoundly impacts patients' everyday lives. The illness's core features include positive and negative symptoms and cognitive impairments. In particular, deficits in the social cognition domain showed a tighter connection to patients’ everyday functioning than the other symptoms. Social remediation interventions have been developed, providing heterogeneous results considering the possibility of generalizing the acquired improvements in patients’ daily activities. In the pilot randomized controlled trial, we investigated the feasibility of combining fifteen daily cognitive and social training sessions with non-invasive brain stimulation to boost the effectiveness of the two interventions. We delivered intermittent theta burst stimulation (iTBS) over the left dorsolateral prefrontal cortex (DLPFC). Twenty-one participants were randomized into four groups, varying for the assigned stimulation condition (real vs. sham iTBS) and the type of cognitive intervention (training vs. no training). Clinical symptoms and social cognition tests were administered at five time points, i.e., before and after the treatment, and at three follow-ups at one, three, and six months after the treatments’ end. Preliminary data show a trend in improving the competence in managing emotion in participants performing the training. Conversely, no differences were found in pre and post-treatment scores for emotion recognition, theory of mind, and attribution of intentions. The iTBS intervention did not induce any additional effect on individuals’ performance. The methodological approach's novelty and limitations of our study are discussed.